Foreign Ownership and Export Performance - Abdel-Malek, Talaat (Journal of International Business Studies, 1974)
This article reports the results of an empirical study which tended to disprove the hypothesis that foreign-owned subsidiaries are less export oriented than domestically-owned firms.